Effect of Utilization Smartphone Regarding Learning Outcomes - Annisa Husnul Khatimah; Rahmi Indiska; Zainal Asril; Ridha Mulyani; Vinni Sabrina (Sekolah Tinggi Agama Islam Pengembangan Ilmu Al-Qur`an Sumatera Barat, 2024)
Own Smartphone There are many benefits, especially in the world of education, but if it is not used properly, it will have a big impact on students, especially on their learning outcomes. In fact, this research is to find out the picture of utilization of Smartphones on student learning outcomes. This research design uses quantitative methods with a correlational approach, the population in this research is a total of seventy-six students, fifteen students were used as a trial, and the sample was sixty-one students. The data analysis technique used is using assumption tests, namely normality tests and homogeneity tests, as well as data analysis or hypothesis tests with the help of the SPSS application. Research results and discussion can be concluded that there is an influence on utilization of Smartphones on student learning outcomes in high school. It is known that the value of the determinant coefficient is large with a large R square amounting to 0.022 x 100, which is 2.2%. This concludes that there is an influence between variable (X) and variable (Y) of 2.2%. This means that there is an influence on utilization of Smartphones on student learning outcomes.